2022
DOI: 10.1128/spectrum.02198-22
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol Mediates Cholesterol Metabolism to Restrict Porcine Deltacoronavirus Infection via Suppression of Transforming Growth Factor β1

Abstract: As an emerging enteropathogenic coronavirus in pigs, porcine deltacoronavirus (PDCoV) causes giant economic loss in the pig industry because of lethal diarrhea and possesses the potential for transmission from animals to humans. Several pieces of evidence have suggested the antiviral potential of cholesterol-25-hydroxylase and importance of cholesterol in viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Among them, we found statin-based molecules and the 25-hydroxycholesterol. These results are quite surprising due to their antiviral effect detected in repositioning against human and veterinarian viruses [48][49][50]. Dynasore and genistein did not present any antiviral effect, which is in discordance with the study of Spiesschaert et al [31].…”
Section: Discussionmentioning
confidence: 54%
“…Among them, we found statin-based molecules and the 25-hydroxycholesterol. These results are quite surprising due to their antiviral effect detected in repositioning against human and veterinarian viruses [48][49][50]. Dynasore and genistein did not present any antiviral effect, which is in discordance with the study of Spiesschaert et al [31].…”
Section: Discussionmentioning
confidence: 54%
“…The molecule 25-hydroxycholesterol (25HC) has been recognized for its potential to inhibit the entry and replication of various coronaviruses, including PEDV and SARS-CoV-2. This inhibitory activity is mainly achieved by interfering with viral fusion and entry into host cells and disrupting viral protein maturation [ 42 , 43 , 44 , 45 , 46 ]. To further investigate the effect of 25HC on pseudovirus rVSV-ΔG-EGFP-S infection, we pretreated Huh7 cells with 25HC at concentrations of 50 μM and 100 μM for 2 h and subsequently infected these cells with rVSV-ΔG-EGFP-S virus.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 25-hydroxycholesterol is an oxidized derivative of cholesterol and has been identified as a potential antiviral compound against several enveloped viruses, such as HIV [ 54 ], Ebola [ 55 ], and Zika [ 56 ]. Recent studies have suggested that 25HC can inhibit the entry and replication of coronaviruses, including PEDV, SARS-CoV-2, and MERS-CoV [ 42 , 43 , 44 , 45 , 57 , 58 ]. The mechanism by which 25HC exerts its antiviral effects on coronaviruses is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral effect of 25HC on SARS-CoV-2 is consistent with the induction of LDs ( 79 ). In our previous study, the early infection of PDCoV (porcine deltacoronavirus) at 8 h to some extent induces the accumulation of LDs, 25HC treatment induces abundant LDs and reduces the replication of PDCoV accompanied by upregulated IFN-β mRNA ( 87 ). The opposite effects of LDs demonstrate its antiviral potential by enhancing the interferon response to viral infection, meanwhile, indicate the inverse mechanisms utilized by viruses to hinder the early antiviral response of organisms.…”
Section: Hc and Cholesterol Metabolismmentioning
confidence: 99%
“…The expression of TGF-β signaling can be dramatically induced by PDCoV infection, which is reversed by 25HC. The application of TGF-β inhibitor reveals its regulatory effect on the genes related to cholesterol metabolism ( 87 ). The thorough mechanism of TGF-β in viral infection is yet to be fully demonstrated, but it might be a potential approach for viral invasion and target for 25HC action.…”
Section: Hc and Transforming Growth Factor-βmentioning
confidence: 99%